THE EFFECT OF FAMILY THERAPY TOWARD PREVENTION OF VIOLENT BEHAVIOR IN CHILD: A LITERATURE REVIEW - Herman, Herman; Kusbaryanto, Kusbaryanto (Jurnal Keperawatan Respati Yogyakarta, 2020)
Family is lasting a social group based on marriage and blood relations. The family plays an important role in the inheritance of the noble values of life for future generations. A healthy family will contribute to the development of a healthy society. This aims to find out the effect of the education system of family therapy on the prevention of violence in children. This research uses relevant Literature review which is reviewed following the search from 3 databases. They are ProQuest, ScienceDirect, and Google Scholar. The search year is limited to the last 5 years from 2014-2019 to ensure the latest included research, using the keyword "therapy family AND Communication AND violent behavior AND child?. This review identifies 6 articles based on inclusion criteria. The article uses a Quasi-experimental design which is 1 article, 3 systematic reviews, and integrative review, 1 quantitative, 1 qualitative, randomized controlled trial. Of the 6 articles selected, 3 articles focus on violent behavior in children and adolescents and 3 articles focus on family communication towards children. Family therapy is the family to learn how to keep a healthy family relationship, communicate effectively with family members, and work cooperatively to solve family problems. This type of therapy is unique because the problem is seen through a wider lens and as part of a complex family system. Communication in the family becomes better when each family member can express what they don?t like and their desires to other family members and then find a solution together